86P A novel ImmunoScore, based on clinical and blood biomarkers, as prognostic model for immunotherapy in NSCLC. (15th December 2019) - Viscardi, G; Sparano, F; Di Liello, R; Casal, G Alonso; Ferreres, R Borras; Bruixola, G; Gambardella, V; Zanaletti, N; Iacovino, M L; Corte, C M Della; Papaccio, F; Fasano, M; et al.
Abstract: Background: Immune checkpoint inhibitors (ICIs) in patients with pretreated advanced NSCLC (aNSCLC) showed an overall survival (OS) benefit over standard chemotherapy in phase III randomized clinical trials (RCTs). Nevertheless, a significant portion of patients do not benefit from ICIs. The identification of biomarkers to select patients most likely to respond to ICIs is greatly needed in clinical practice. The role of baseline clinical and blood biomarkers as prognostic of response to ICIs was investigated in patients with aNSCLC and a prognostic ImmunoScore is defined. Methods: We retrospectively reviewed clinical data of aNSCLC patients consecutively treated with single agents anti PD-1 or anti PD-L1 as 2nd (81.8%) or ≥ 3rd (18.2%) line at University Hospitals of Valencia and Naples. ECOG PS, sites of metastases, neutrophil to lymphocyte ratio (NLR), LDH and albumin levels were recorded at baseline. The impact of these variables on PFS and OS was assessed through survival analyses (Kaplan Meier method), univariate (log rank test) and multivariate analyses (Cox proportional hazard model). Results: The analysis included 132 pts. Median PFS and OS were 3 (95% CI 2.74-3.26) and 9 (95% CI 5.90-12.02) months respectively. The univariate analysis for PFS showed that baseline NLR>4 (p = 0.001), albumin <3.5 mg/dl (p = 0.005), PS > 1 (HR 2.96, p < 0.001) and liver metastases (HR 1.72, p = 0.002) were associated with worse outcome. A trend for significance was observed for LDH >400 U/l (p = 0.089). The multivariate analysis for PFS confirmed as statistically significant independent negative prognostic factors PS > 1 (p = 0.001) and liver metastases (p = 0.011). Finally, according to PS, liver metastases, NLR and albumin three different prognostic groups at high (3-4 RF), intermediate (1-2 RF) and low (0 RF) risk for OS were defined. Median OS was respectively 5 (95% CI 3.45-6.55), 7 (95% CI 4.98-9.02) and 23 (95% CI 16.53-29.47) months (p < 0.001). Conclusion: Baseline evaluation of clinical and blood biochemical parameters can be a tool to predict outcome in patients treated with ICIs for aNSCLC. Moreover, combining them in ImmunoScore may help to identify pts candidates to second or subsequent Iines of therapy who most likely will benefit from ICIs. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.